Reconstructing undersampled MR Images by utilizingprincipal-component-analysis-based pattern recognition - Zong, Fangrong; D’Eurydice, Marcel Nogueira; Galvosas, Petrik (Diffusion Fundamentals, 2014)
Compressed sensing technique is a recent framework for signal sampling and recovery. It allows signal acquisition with less sampling than required by Nyquist-Shannon theorem and reduces data acquisition time in MRI. When the sampling rate is low, prior knowledge is essential to reconstruct the missing features. In this paper, a different reconstruction method is proposed by using the principal component analysis based on pattern recognition. The experiments demonstrate that this method can reduce aliasing artefacts and achieve a high peak signal-to-noise ratio compared to a compressed sensing reconstruction.